The specialization of judicial bodies: Agrarian courts. The experience in Ibero-American countries (Revista Española de Estudios Agrosociales y Pesqueros, 2023)
Agrarian law is also reflected in judicial organisation: there are agrarian courts in many countries, and in particular in the Latin American judicial panorama. This matter has been the object of attention in numerous works and studies by international organisations and, in particular, by the FAO (United Nations Food and Agriculture Organisation), and the viability - under parameters of efficiency and efficacy - of deploying organic-procedural instruments that respond to the conflicts that may arise in the application of the diversity of rules that regulate it, can be considered in terms of specialisation. In accordance with the planned legislation on organisational efficiency which foresees the creation of Courts of First Instance - which will replace the so-called Courts as the first step in the judicial organisation - and which also encourages the specialisation of the Sections of the Provincial Courts, it is worth considering to what extent specialisation, via concentration in the distribution of cases, in agricultural matters (essentially, rural leases, restitution of subsidies, etc.) can contribute to a faster response, and to achieving more unified and predictable judicial criteria.
Keywords: Agrarian law; Agrarian trials; specialisation